The effects of soluble corn fibre and isomaltooligosacharides on blood glucose, insulin, digestion and fermentation in healthy young males and females - Ryan P. Lowery; Jacob M. Wilson; Andrew Barninger; Matthew H. Sharp; Christopher Irvin; Matthew Stefan; William A. Wallace; Gabriel J. Wilson; Michael D. Roberts; Ronald Wagner (Journal of Metabolic Health, 2018)
Dietary fibre refers to nutrients in the diet that gastrointestinal enzymes do not digest. If properly labelled, dietary fibres should not significantly elevate blood glucose or insulin and should ferment in the large intestine. Because of the recent rise in low-carbohydrate products on the market, consumers use these various fibres without adequate knowledge concerning whether or not these ingredients affect any blood parameters and constitute a dietary fibre. The aim of this study was to examine the impact of isomaltooligosaccharides (IMO) as compared to soluble corn fibre (SCF) consumption on blood glucose, insulin and breath hydrogen responses in healthy young men and women. After an overnight fast, nine individuals consumed 25 g of either placebo (PLA), IMO or SCF. Breath hydrogen was significantly higher in the SCF condition than in the IMO and PLA at 90, 120, 150 and 180 min (p  0.0001). Blood glucose and insulin were higher in the IMO condition (p  0.0001) at 30 min compared to the SCF or PLA conditions, which were not significantly different from each other. These data suggest that IMO does not constitute a dietary fibre and instead should be explored as a slow-digesting carbohydrate.